The role of genetics in pre-eclampsia and potential pharmacogenomic interventions - Williams, Paula Juliet; Morgan, Linda (Dove Press, 2012)
The pregnancy-specific condition pre-eclampsia not only affects the health of mother and baby during pregnancy but also has long-term consequences, increasing the chances of cardiovascular disease in later life. It is accepted that pre-eclampsia has a placental origin, but the pathogenic mechanisms leading to the systemic endothelial dysfunction characteristic of the disorder remain to be determined. In this review we discuss some key factors regarded as important in the development of pre-eclampsia, including immune maladaptation, inadequate placentation, oxidative stress, and thrombosis. Genetic factors influence all of these proposed pathophysiological mechanisms. The inherited nature of pre-eclampsia has been known for many years, and extensive genetic studies have been undertaken in this area. Genetic research offers an attractive strategy for studying the pathogenesis of pre-eclampsia as it avoids the ethical and practical difficulties of conducting basic science research during the preclinical phase of pre-eclampsia when the underlying pathological changes occur. Although pharmacogenomic studies have not yet been conducted in pre-eclampsia, a number of studies investigating treatment for essential hypertension are of relevance to therapies used in pre-eclampsia. The pharmacogenomics of antiplatelet agents, alpha and beta blockers, calcium channel blockers, and magnesium sulfate are discussed in relation to the treatment and prevention of pre-eclampsia. Pharmacogenomics offers the prospect of individualized patient treatment, ensuring swift introduction of optimal treatment whilst minimizing the use of inappropriate or ineffective drugs, thereby reducing the risk of harmful effects to both mother and baby.